2019
DOI: 10.1002/lio2.269
|View full text |Cite
|
Sign up to set email alerts
|

Chronic inflammatory response in the rat lung to commonly used contrast agents for videofluoroscopy

Abstract: Objectives Contrast agents (CAs) are essential for upper gastrointestinal and videofluoroscopic swallow studies (VFSSs). Recently, we reported that small amounts of Ba aspiration caused severe acute lung inflammation in a rodent model. However, the underlying molecular biological mechanisms of chronic response to CA aspiration remain unclear. The aims of this study were to explore the underlying molecular biological mechanisms of the chronic response to three kinds of CA aspiration on the lung. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Within 30 days, histopathological findings showed thickened bronchiolar walls with staining positive for CD3+ lymphocytes and thickened alveolar walls staining positive for myeloperoxidase (MPO) (+) granulocytes and macrophages for continued chronic inflammation of the respiratory system. 3,4 Although incidence of barium aspiration can be rare with varying prognosis, prevention should always be considered. Alternative diagnostic work up in those with risk factors for aspiration include ultrasound, endoscopy, magnetic resonance imaging (MRI), CT, positron emission tomography (PET) scan, functional endoscopic evaluation of swallowing, or even video fluoroscopic modified barium swallow.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Within 30 days, histopathological findings showed thickened bronchiolar walls with staining positive for CD3+ lymphocytes and thickened alveolar walls staining positive for myeloperoxidase (MPO) (+) granulocytes and macrophages for continued chronic inflammation of the respiratory system. 3,4 Although incidence of barium aspiration can be rare with varying prognosis, prevention should always be considered. Alternative diagnostic work up in those with risk factors for aspiration include ultrasound, endoscopy, magnetic resonance imaging (MRI), CT, positron emission tomography (PET) scan, functional endoscopic evaluation of swallowing, or even video fluoroscopic modified barium swallow.…”
Section: Discussionmentioning
confidence: 99%
“…Barium is a foreign body in the lung, which causes chronic pulmonary inflammation. 3 Barium studies are indicated for any digestive complaints centering around dysphagia. Barium sulfate is an insoluble agent that is used to visualize the gastrointestinal (GI) tract via a bolus that is ingested and later excreted in the feces undigested.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Iohexol (Omnipaque; Daiichi-Sankyo) was used as a contrast agent in VFSS since it has low pulmonary toxicity when aspirated into the lung. 22 , 23 To add viscosity to the contrast agent, a thickener (Toromeiku SP; Meiji) was used. First, 5 mL of a moderately thickened liquid (200 mPaċs) was administered, followed by 5 mL of mildly thickened liquid (100 mPaċs) and 5 mL of thin liquid (10 mPaċs).…”
Section: Methodsmentioning
confidence: 99%
“…Videofluorographic studies were performed and recorded in the lateral view. Iohexol (Omnipaque; Daiichi‐Sankyo) was used as a contrast agent in VFSS since it has low pulmonary toxicity when aspirated into the lung 22 , 23 . To add viscosity to the contrast agent, a thickener (Toromeiku SP; Meiji) was used.…”
Section: Methodsmentioning
confidence: 99%